Flow sorting of C-genome chromosomes from wild relatives of wheat Aegilops markgrafii, Ae. triuncialis and Ae. cylindrica, and their molecular organization - Molnár, István; Vrána, Jan; Farkas, András; Kubaláková, Marie; Cseh, András; Molnár-Láng, Márta; Doležel, Jaroslav (Annals of botany, 2015)
BACKGROUND AND AIMS: Aegilops markgrafii (CC) and its natural hybrids Ae. triuncialis (U(t)U(t)C(t)C(t)) and Ae. cylindrica (D(c)D(c)C(c)C(c)) represent a rich reservoir of useful genes for improvement of bread wheat (Triticum aestivum), but the limited information available on their genome structure and the shortage of molecular (cyto-) genetic tools hamper the utilization of the extant genetic diversity. This study provides the complete karyotypes in the three species obtained after fluorescent in situ hybridization (FISH) with repetitive DNA probes, and evaluates the potential of flow cytometric chromosome sorting. METHODS: The flow karyotypes obtained after the analysis of 4',6-diamidino-2-phenylindole (DAPI)-stained chromosomes were characterized and the chromosome content of the peaks on the flow karyotypes was determined by FISH. Twenty-nine conserved orthologous set (COS) markers covering all seven wheat homoeologous chromosome groups were used for PCR with DNA amplified from flow-sorted chromosomes and genomic DNA. KEY RESULTS: FISH with repetitive DNA probes revealed that chromosomes 4C, 5C, 7C(t), T6U(t)S.6U(t)L-5C(t)L, 1C(c) and 5D(c) could be sorted with purities ranging from 66 to 91 %, while the remaining chromosomes could be sorted in groups of 2-5. This identified a partial wheat-C-genome homology for group 4 and 5 chromosomes. In addition, 1C chromosomes were homologous with group 1 of wheat; a small segment from group 2 indicated 1C-2C rearrangement. An extensively rearranged structure of chromosome 7C relative to wheat was also detected. CONCLUSIONS: The possibility of purifying Aegilops chromosomes provides an attractive opportunity to investigate the structure and evolution of the Aegilops C genome and to develop molecular tools to facilitate the identification of alien chromatin and support alien introgression breeding in bread wheat.
Keywords: Sequence Homology, Nucleic Acid; lipnicovité; Aegilops markgrafii; conserved orthologous set markers; průtoková cytometrie; Indoles; Ae. cylindrica; indoly; metafáze; karyotypizace; In Situ Hybridization, Fluorescence; Triticum; Flow Cytometry; Chromosomes, Plant; genomic in situ hybridization; GISH; flow cytometric chromosome sorting; karyotyp; Ae. triuncialis; hybridizace in situ fluorescenční; Poaceae; fluorescence in situ hybridization; pšenice; physical mapping; COS; Conserved Sequence; sekvenční homologie nukleových kyselin; Triticum aestivum; Metaphase; Karyotyping; FISH; genom rostlinný; Genome, Plant; wheat; goatgrass; chromozomy rostlin; konzervovaná sekvence; Karyotype